2017
DOI: 10.1371/journal.pone.0186765
|View full text |Cite
|
Sign up to set email alerts
|

Household food production is positively associated with dietary diversity and intake of nutrient-dense foods for older preschool children in poorer families: Results from a nationally-representative survey in Nepal

Abstract: BackgroundNutrition-sensitive interventions supporting enhanced household food production have potential to improve child dietary quality. However, heterogeneity in market access may cause systematic differences in program effectiveness depending on household wealth and child age. Identifying these effect modifiers can help development agencies specify and target their interventions.ObjectiveThis study investigates mediating effects of household wealth and child age on links between farm production and child d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 36 publications
4
43
1
1
Order By: Relevance
“…Consumption of fruits and vegetables improves micronutrient status and immune function and may support child growth (Aguayo, Nair, Badgaiyan, & Krishna, ). A previous study in Ethiopia also reported that higher vegetable and fruit dietary consumption is associated with increased LAZ and reduced risk of stunting (Melaku et al, ), consistent with findings from Nepal and northern Ghana (Mulmi et al, ; Saaka, Osman, & Hoeschle‐Zeledon, ).…”
Section: Discussionsupporting
confidence: 76%
“…Consumption of fruits and vegetables improves micronutrient status and immune function and may support child growth (Aguayo, Nair, Badgaiyan, & Krishna, ). A previous study in Ethiopia also reported that higher vegetable and fruit dietary consumption is associated with increased LAZ and reduced risk of stunting (Melaku et al, ), consistent with findings from Nepal and northern Ghana (Mulmi et al, ; Saaka, Osman, & Hoeschle‐Zeledon, ).…”
Section: Discussionsupporting
confidence: 76%
“…This shows that as households increase the number of food groups produced, the probability of improving dietary diversity and food security increases. This suggests that an increase in the diversification of food production increases the food security which is consistent with previous studies on the relationship between food security and farm production diversity (Islam et al 2018;Hirvonen and Hoddinott 2017;Mulmi et al 2017;Sibhatu et al 2015).…”
Section: B Agricultural Production and Other Non-farm Activitiessupporting
confidence: 92%
“…This formed part of the motivation of this study, which was to analyze the nutritional outcome of households living in remote rural communities. Some studies [74,75] acknowledged the importance of focusing on the more vulnerable groups in such research.…”
Section: Discussionmentioning
confidence: 99%